Surgical repair of conjunctival defects: perspectives and limitations - M.B. Gushсhina; A.V. Tereshchenko; A.V. Gushchin; D.S. Afanasyeva (РМЖ "Клиническая офтальмология")
M.B. Gushсhina1, A.V. Tereshchenko2, A.V. Gushchin3, D.S. Afanasyeva4 1National Medical Research Center Central Research Institute of Dentistry and Orthodontic Surgery, Moscow, Russian Federation 2Kaluga Branch of the S. Fyodorov Eye Microsurgery Federal State Institution, Kaluga, Russian Federation 3I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, Russian Federation 4V.P. Vykhodtsev Clinical Ophthalmological Hospital, Omsk, Russian Federation Background: conjunctival disorders are associated with multiple anatomical functional impairments of the eye and ocular adnexa. Rehabilitation of these patients implies the recovery of both macroanatomy and functions of damaged tissues and structures. Aim: to analyze the outcomes of surgical repair of conjunctival defects from the viewpoint of the recovery of ocular anatomy and functions and ocular adnexa. Patients and Methods: a retrospective analysis of the outcomes of surgical repair of conjunctival defects using full-thickness and/or split-thickness autografts of the labial or cheek mucosa in 27 patients. The mean age of participants was 36.86±19.46 years. Follow-up was 1.5 to 6.5 years. The patients were divided into two groups. Group 1 included 21 patients with local symblepharon. Group 2 included patients with subtotal or total conjunctival adhesions of a healthy eye (group 2A, n=3) or in anophthalmia (group 2B, n=4). Results: surgical repair of conjunctival defects provided a complete anatomical functional rehabilitation of patients with local symblepharon and esthetical rehabilitation of patients with subtotal conjunctival adhesions or  ankyloblepharon in anophthalmia, whereby allowing keratoprosthesis in a patient with one potentially seeing eye. Meanwhile, we failed to achieve a complete functional rehabilitation and recovery of vision in patients with a potentially seeing eye due to the loss of the palisades of Vogt and/or tear-producing conjunctival structures. Conclusions: surgical repair of conjunctival defects using the technique proposed completely recovers the macroanatomy of the conjunctival fornices and sac and, therefore, improves eyeball and eyelid mobility. However, impossibility of recovering histology in virtually complete loss of native conjunctiva does not allow complete rehabilitation of patients with symblepharon or ankyloblepharon of a potentially seeing eye. Keywords: symblepharon, anlyloblepharon, limbal deficiency, tear production, corneal leucoma, mucosal autograft. For citation: Gushсhina M.B., Tereshchenko A.V., Gushchin A.V., Afanasyeva D.S. Surgical repair of conjunctival defects: perspectives and limitations. Russian Journal of Clinical Ophthalmology. 2022;22(2):137–144 (in Russ.). DOI: 10.32364/2311-7729-2022-22-2-137-144.